Understanding Wave Attenuation Across Marshes: Insights from Numerical Modeling - Madeline R. Foster-Martinez; Ioannis Y. Georgiou; Duncan M. FitzGerald; Zoe J. Hughes; Alyssa Novak; Md Mohiuddin Sakib (Journal of Marine Science and Engineering, 2025)
Marsh vegetation dampens wave energy, providing protection to coastal communities from storms. A new modeling framework was applied to study wave height evolution over the saltmarsh bordering Newbury, MA. A regional Delft3D hydrodynamic model generated wind driver waves in the open water portions of the study area, which were then one-way coupled with an analytical model, the Marsh Transect Wave Attenuation (MTWA) model, which tracked wave evolution along select transects throughout the marsh. Field observations of vegetation and wave height evolution were used to calibrate MTWA. Seven scenarios were run covering a range of possible future management and environmental conditions, in addition to projected sea level rise. Results underscore the importance of vegetation and elevation to wave attenuation.